Maria Tallchief America's prima ballerina - Tallchief, Maria 1925-2013; Kaplan, Lawrence D. 1950- (Henry Holt & Company, 2015)
Maria Tallchief was George Balachine's muse for twenty years and his wife for six. Together they made the New York City Ballet an essential part of American culture, with his choreography and her dazzling, technically bravura dancing. Tallchief received the Kennedy Center Honors in 1996.
Keywords: Tallchief, Maria; Tallchief, Maria -- 1925-2013; Ballerinas -- United States -- Biography; Indian ballerinas -- United States -- Biography; Osage Indians -- United States -- Biography; USA; Autobiografie